2012
DOI: 10.5897/ajb12.829
|View full text |Cite
|
Sign up to set email alerts
|

Examination of rheological and physicochemical characteristics in Lithuanian honey

Abstract: The aim of the study was to determine the effect of the biological origin and temperature on rheological and physicochemical characteristics of honey. The honey of the selected varieties differed in color, scent, microstructure, total acidity, moisture, and pH. The level of moisture statistically significantly correlated with the rheological characteristics. The highest total acidity was a characteristic of forest and buckwheat honey, and the lowest of acacia honey. The lowest pH value (3.76) was found in fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
1
6
1
2
Order By: Relevance
“…The values of the complex viscosity of the analysed media are similar to the values of the dynamic viscosity for instance, the relative differences between the average values of dynamic viscosity and complex viscosity for rape honey was 3.2% (Bakier et al, 2016). Stelmakienė et al (2012) reported significant differences in the rheological properties (thixotropy and consistency index) of Lithuanian commercial rapeseed honey, between the temperatures of 30 and 40°C, as well as between 30 and 50°C, contrary to present results. Interestingly, on the one hand, Lithuanian rapeseed honey exhibited at 30°C the highest consistency coefficient compared to other honey varieties, and it also showed elastic properties.…”
Section: Resultscontrasting
confidence: 53%
See 2 more Smart Citations
“…The values of the complex viscosity of the analysed media are similar to the values of the dynamic viscosity for instance, the relative differences between the average values of dynamic viscosity and complex viscosity for rape honey was 3.2% (Bakier et al, 2016). Stelmakienė et al (2012) reported significant differences in the rheological properties (thixotropy and consistency index) of Lithuanian commercial rapeseed honey, between the temperatures of 30 and 40°C, as well as between 30 and 50°C, contrary to present results. Interestingly, on the one hand, Lithuanian rapeseed honey exhibited at 30°C the highest consistency coefficient compared to other honey varieties, and it also showed elastic properties.…”
Section: Resultscontrasting
confidence: 53%
“…Interestingly, on the one hand, Lithuanian rapeseed honey exhibited at 30°C the highest consistency coefficient compared to other honey varieties, and it also showed elastic properties. On the other hand, at temperatures of 40 and 50°C it demonstrated pseudoplastic substance properties (Stelmakienė et al, 2012). At the highest temperature (50°C) used in the present study, the average values of the investigated textural properties were 64.74 g, 0.67 mJ, 26.51 g, and 14.16 g, respectively.…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…They suggested that at very low shear rate, similar to those employed in this work, blood exhibits shear thinning behaviour, but as shear rate increases, the non-Newtonian behaviour gradually diminishes. Stelmakeiene and coworkers, [19], Cohen and Weihs, [20], Mossel and coworkers, [21] and Munro, [22], all reported that honey exhibited thixotropic rheological behaviour. However, this is contrary to Zaitoun and coworkers [23], who concluded that honey exhibits Newtonian behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…From the rheograms (Figure 3), it can be observed that honey turns completely Newtonian from 10% adulteration with water. Other studies also show that adulterating honey with water leads to fermentation of the monosaccharides in honey leading to sour taste [19]. For better understanding of the rheograms, curve fits were carried out using both the newly derived Structural Kinetic model and the amended Carreau Yasuda model.…”
Section: Resultsmentioning
confidence: 99%